Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
(x+3).(2x-18)=0
=>x+3=0 hoặc 2x-18 =0
+)x+3=0
x=-3
+)2x-18=0
2x =18
x =9
Vậy x \(\in\)\(_{\left\{-3;9\right\}}\)
a) \(\frac{5}{12}-\frac{3}{-16}+\frac{3}{4}\)
\(=\frac{5}{12}-\left(-\frac{3}{16}\right)+\frac{3}{4}\)
\(=\frac{5}{12}+\frac{3}{6}+\frac{3}{4}\)
\(=\frac{20+9+36}{48}\)
\(=\frac{65}{48}\)
Mấy câu kia lát làm :))
\(a.2x+35=x-27\)
\(\Leftrightarrow2x-x=-27-35\)
\(\Rightarrow x=-62\). Vậy \(x=-62\)
\(b.2x-41=3x+\left(-23\right)\)
\(\Leftrightarrow2x-3x=-23+41\)
\(\Leftrightarrow-x=18\)
\(\Rightarrow x=-18\). Vậy \(x=-18\)
\(c.4\left(x-3\right)-3\left(x+5\right)=45.\left(-2\right)-34\)
\(\Leftrightarrow4x-12-3x-15=-124\)
\(\Leftrightarrow4x-3x=-124+12+15\)
\(\Rightarrow x=-97\). Vậy \(x=-97\)
\(d.\left(x+3\right)\left(2x-18\right)=0\)
\(\Leftrightarrow\hept{\begin{cases}x+3=0\\2x-18=0\end{cases}\Rightarrow\hept{\begin{cases}x=-3\\x=9\end{cases}}}\). Vậy \(x=-3;9\)
\(A=2.3+3.4.+4.5+...+34.35\)
\(3A=2.3.\left(4-1\right)+3.4.\left(5-2\right)+4.5.\left(6-3\right)+...+34.35.\left(36-33\right)\)
\(=2.3.4-1.2.3+3.4.5-2.3.4+4.5.6-3.4.5+...+34.35.36-33.34.35\)
\(=34.35.36-1.2.3\)
Suy ra \(A=14278\)